Profile of the patients suffering from non-communicable diseases attending outpatient department of an urban health training center- a cross sectional study - Naidu, Abhishek; Gurav, Ravindra; Yadav, Amit (International Journal Of Community Medicine And Public Health, 2024)
Background: Non-communicable diseases continue to be an important public health problem in India. These diseases are responsible for a major proportion of morbidity and mortality. In view of this, study was conducted among patients suffering from non-communicable diseases attending outpatient department of an urban health training center of a medical college to know their profile. Methods: A cross-sectional study was conducted in the month of September, 2023 at an urban health training center. All the patients suffering from non-communicable diseases attending outpatient department during above month were included in the study using purposive sampling method. Predesigned and pretested proforma was used to collect the data. Data was analyzed using Microsoft Excel and appropriate statistical methods. The statistical level of significance was fixed at p<0.05. Results: 4670 new patients attended outpatient department, of which 269 (05.76%) were suffering from non-communicable diseases. 136 (52.92%) were suffering from hypertension, 105 (40.86%) were of diabetes, 07 (02.72%) were of stroke and 09 (03.50%) were of other non-communicable diseases. 12 (04.46%) patients were suffering from both hypertension and diabetes. 131 (50.97%) were above 60 years of age. 139 (54.09%) were males and 118 (45.91%) were females. 50 (19.46%) patients were illiterate while 207 (80.54%) were literate (p<0.05). 42 (16.34%) patients were having family history of non-communicable diseases. 40 (15.56%) and 62 (24.12%) patients were doing yoga and exercise respectively. 77 (29.96%) patients were smokers or consuming tobacco or alcohol. Conclusions: The growing problem of non-communicable diseases can be effectively controlled by empowerment of community through effective health education, utilizing services of trained health care workers, advanced health care services and social insurance.